Mitigating microgrid voltage fluctuation using battery energy storage system with improved particle swarm optimization - Keerachat Tantrapon (2020)
© 2019 The variability and intermittency of light intensity, caused by cloud movement and weather conditions, can create fluctuation in the photovoltaic (PV) power generation. In a microgrid with a high PV penetration, these can affect severe microgrid voltage fluctuation problem. However, the battery energy storage system (BESS) is an equipment that can be used to smooth PV fluctuation and enhance the flexibility of the microgrid. In this paper, an improved particle swarm optimization (I-PSO) is developed to mitigate the voltage fluctuation by optimizing both BESS active and reactive power. The I-PSO is developed and implemented in MATLAB, while the time sweep load flow is calculated by using DIgSILENT PowerFactory. The proposed method is tested on the practical 22 kV Mae Sa Riang microgrid in Thailand which has encountered from voltage fluctuation problem. The simulation results show that the I-PSO is more effective in determining the optimal BESS operation and mitigating the PV voltage fluctuation than the PV smoothing mode in the microgrid.